Endothelial Progenitor Cells Physiology and Metabolic Plasticity in Brain Angiogenesis and Blood-Brain Barrier Modeling - Malinovskaya, Natalia A.; Komleva, Yulia K.; Salmin, Vladimir V.; Morgun, Andrey V.; Shuvaev, Anton N.; Panina, Yulia A.; Boitsova, Elizaveta B.; Salmina, Alla B. (Frontiers in Physiology, 2016)
Currently, there is a considerable interest to the assessment of blood-brain barrier (BBB) development as a part of cerebral angiogenesis developmental program. Embryonic and adult angiogenesis in the brain is governed by the coordinated activity of endothelial progenitor cells, brain microvascular endothelial cells, and non-endothelial cells contributing to the establishment of the BBB (pericytes, astrocytes, neurons). Metabolic and functional plasticity of endothelial progenitor cells controls their timely recruitment, precise homing to the brain microvessels, and efficient support of brain angiogenesis. Deciphering endothelial progenitor cells physiology would provide novel engineering approaches to establish adequate microfluidically-supported BBB models and brain microphysiological systems for translational studies.